2000
DOI: 10.3171/jns.2000.93.2.0265
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of regional cerebral blood flow: experimental and clinical validation of a novel thermal diffusion microprobe

Abstract: The novel TD microprobe provides a sensitive, continuous, and real-time assessment of intraparenchymal rCBF in absolute flow values that are in good agreement with sXe-rCBF measurements. This study provides the basis for the integration of TD-rCBF into multimodal monitoring of patients who are at risk for secondary brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(102 citation statements)
references
References 41 publications
2
99
0
1
Order By: Relevance
“…Thermal diffusion flowmetry is so far the only technique, which allows for CBF monitoring in a feasible and user-friendly way directly at the bedside and there is evidence that symptomatic vasospasm after aSAH can be detected by the method 7,8 . However, its clinical application is limited because measurement drifts have been reported over the 30-minute measurement cycle and between automatically performed recalibrations 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal diffusion flowmetry is so far the only technique, which allows for CBF monitoring in a feasible and user-friendly way directly at the bedside and there is evidence that symptomatic vasospasm after aSAH can be detected by the method 7,8 . However, its clinical application is limited because measurement drifts have been reported over the 30-minute measurement cycle and between automatically performed recalibrations 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, thermal diffusion flowmetry for continuous bedside assessment of CBF was introduced and potential clinical benefits were demonstrated in patients with symptomatic vasospasm after aSAH 7,8 . However, the clinical application remains limited because of reduced reliability of CBF measurements in patients with fever and hemodynamic instability 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Laser Doppler flowmetry uses the same principle as TCD but has the probe placed intracranially through a burr hole and measures the concentration of red blood cells and their velocity generating a flow signal to provide a qualitative estimate of regional cerebral blood flow but has a limited sample volume [46]. The thermal diffusion method utilizes an intraparenchymal probe with a thermistor and a temperature sensor and measures the thermal gradient between the distal thermistor that his heated by 2°C and the proximal temperature sensor and provides a quantified regional cerebral blood flow measurement in ml/100 g/min [47]. CBF monitoring has been studies in traumatic brain injury, and thresholds of injury and ischemia have been found to correlate with regional brain tissue oxygenation.…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…A probe that is placed in the brain parenchyma and allows stable CBF readings based on the principles of thermodilution in perfused tissues has now been cleared by the Food and Drug Administration (FDA) recently (Q flow 500 probe, Bowman Perfusion Monitor, Hemedex, Cambridge, MA). A good correlation has been shown with stable Xenon-CT. 91 It is expected that this method will face critical clinical testing during the next few years.…”
Section: Traumatic Head Injurymentioning
confidence: 99%